Effect of the COVID-19 Pandemic on the Pediatric Emergency Department Flow. (20th December 2023) - Rivera-Sepulveda, Andrea; Maul, Timothy; Dong, Katherine; Crate, Kylee; Helman, Talia; Bria, Corinne; Martin, Lisa; Bogers, Kimberly; Pearce, Joseph W.; Glass, Todd F.
Abstract: Objective: The aim of this study was to determine how the early stages of the coronavirus disease 2019 (COVID-19) pandemic affected the use of the pediatric emergency department (PED). Methods: Cross-sectional study of PED visits during January through April, 2016-2020. Data included: total PED visits, emergency severity index (ESI), disposition, chief complaint, age (months), time from first provider to disposition (PTD), and PED length of stay (PED-LOS). P -value <0.01 was statistically significant. Results: In total, 67, 499 visits were reported. There was a significant decrease in PED visits of 24-71% from March to April 2020. Chief complaints for fever and cough were highest in March 2020; while April 2020 had a shorter mean PED-LOS (from 158 to 123 min), an increase of admissions (from 8% to 14%), a decrease in ESI 4 (10%), and an increase in ESI 3 (8%) ( P < 0.001). There was no difference in mean monthly PTD time. Conclusions: Patient flow in the PED was negatively affected by a decrease in PED visits and increase in admission rate that may be related to higher acuity. By understanding the interaction between hospital processes on PEDs and patient factors during a pandemic, we are able to anticipate and better allocate future resources.